Coordination chemistry of the benzaldehyde(1r)(-)fenchone azine and derivatives fench=nn=c(h)c6 h4 x (x = h, cl, br, ome or no2 in the meta or para positions) with palladium - Ahmad Mustaffa, Md Isa Illyas, L. Shaw Bernard, D. Perera Sarath, (N/A, 2009)
Coordination chemistry of the benzaldehyde(1r)(-)fenchone azine and derivatives fench=nn=c(h)c6 h4 x (x = h, cl, br, ome or no2 in the meta or para positions) with palladium by Ahmad Mustaffa, Md Isa Illyas, L. Shaw Bernard, D. Perera Sarath,